New Synthesis of 3-Aminohydantoins via Condensation of Hydrazines with Isocyanates Derived from α-Amino Esters - Bouchnak, Houda; Ollevier, Thierry; Kraïem, Jamil (SynOpen, 2023)
A new, simple, and efficient method for the synthesis of 3-aminohydantoins was reported in two steps, starting from the corresponding l-amino esters. Commercially available α-amino esters were converted into the corresponding isocyanate derivatives, which were then subjected to the condensation reaction with hydrazine hydrate and arylhydrazines, in the presence of DMAP and DIPEA. This method provides the corresponding 3-aminohydantoins in moderate and good yields under a simple and practical protocol.
Keywords: 3-aminohydantoins; α-amino esters; hydrazines; isocyanates; cyclization